2015
DOI: 10.3389/fnana.2015.00119
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric projections of the arcuate fasciculus to the temporal cortex underlie lateralized language function in the human brain

Abstract: The arcuate fasciculus (AF) in the human brain has asymmetric structural properties. However, the topographic organization of the asymmetric AF projections to the cortex and its relevance to cortical function remain unclear. Here we mapped the posterior projections of the human AF in the inferior parietal and lateral temporal cortices using surface-based structural connectivity analysis based on diffusion MRI and investigated their hemispheric differences. We then performed the cross-modal comparison with func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 65 publications
(95 reference statements)
6
33
2
Order By: Relevance
“…We observed distinct differences in the inferior parietal cortex around the supra-marginal gyrus, the lateral temporal cortex, and in the lateral frontal cortex. Takaya et al (2015) showed in a study group of right-handers, that functional connectivity along the arcuate fasciculus is asymmetric. Similar to Takaya et al (2015), our results also show the highest displacement for right-handers in the inferior parietal cortex and the lateral temporal cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed distinct differences in the inferior parietal cortex around the supra-marginal gyrus, the lateral temporal cortex, and in the lateral frontal cortex. Takaya et al (2015) showed in a study group of right-handers, that functional connectivity along the arcuate fasciculus is asymmetric. Similar to Takaya et al (2015), our results also show the highest displacement for right-handers in the inferior parietal cortex and the lateral temporal cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Takaya et al (2015) showed in a study group of right-handers, that functional connectivity along the arcuate fasciculus is asymmetric. Similar to Takaya et al (2015), our results also show the highest displacement for right-handers in the inferior parietal cortex and the lateral temporal cortex. This indicates that our functional alignment approach reveals the functional variability in language related regions.…”
Section: Discussionmentioning
confidence: 99%
“…B. Cortical projection of tractography calculated by the surface-based analysis. Used with permission (29). …”
Section: Figmentioning
confidence: 99%
“…Takaya et al evaluated the tractography and its cortical projections by using surface-based analysis in healthy subjects (Fig. 4), and showed the asymmetric distribution of the arcuate fasciculus projections in the inferior parietal and lateral temporal cortices, extended more in the left than the right hemisphere (29). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation